SEJARAH PERKEMBANGAN TRANSPORTASI NAYOR DI KABUPATEN SUKABUMI DALAM UPAYA PENGEMBANGAN KARAKTER DAN EKONOMI KREATIF PADA MASA ORDE BARU - Muhammad widyanto; Triwahana (KARMAWIBANGGA Historical Studies Journal, 2022)
The nayor is a kind of traditional transportation that has great popularity up until the New Order era, when it becomes a symbol in the has become increasingly unusual because there are so many public transit options available right now. In an effort to foster character and the creative economy during the New Order era, the goal of this study was to learn the history of the development of nayor transit in Sukabumi Regency. The analysis and data gathering for this study included field observations, interviews, documentation, and literature reviews. According to the findings of important research, the nayor is atraditional vehicle that was first found in Cibadak, Sukabumi, West Java. During the New Order era, Nayor had achieved the pinnacle of its splendor and served the locals as a dependable mode of transportation. The community makes use of Nayor by using it for transportation or tours, creating unique routes for it as a tourist attraction, and hosting events with it. Nayor is able to connect with numerous isolated villages in the emerging creative economy. The factors that made nayor transportation popular and a popular tourist destination throughout the new order era defined the company's growth in terms of its contribution to the creative economy during that time.